The GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PERTUMBUHAN DAN PERKEMBANGAN BALITA - Ni Made Dita Iswary Sukadana; Nur Dwi Noviyanto (Jurnal Online Keperawatan Indonesia, 2020)
The success of monitoring or early detection and stimulation of growth and development of children cannot be separated from the role of health professionals and parents especially the mother. The late of growth and development is a frequent problemecountered in the community, yet sometimes it gets improper treatment. The obstacles encountered in the field are the lack of implementation of early detection of growth and development of children at the age 1-5 years. Children at this age no longer visit to “posyandu” because the mothers have perception that the children have been given compulsory immunization. seeing the above phenomenon, researchers conducted study to know the description of the level of knowledge of mother`s about the growth and development of toddlers in the working area public health center of banguntapan II bantul, yogyakarta. This research uses descriptive quantitative method. The subjects of this study are all mothers having children with the age 1-5 years. The sampling technique used in this study is total sampling. This research conducted in Puskesmas II Banguntapan Bantul Yogyakarta with sampels as many as 43 mothers. From the result of the study , it is found that from 43 respondents who have children with the age 36-48 months ;in a good category is 31 respondents (72.1%), a sufficient category is 12 respondents (27.9%) and a lack category is 0 respondents (0%). The conclusion of this study are the description of mother`s knowledge level about toddlers growth at the age of 1-5 years in the working area public health center of the Banguntapan ii bantul yogyakarta, the majority are in category of good knowledge, as many as 31 respondents (72.1%).